Integrating Occupational Stress, Social Support, and Work Family Conflict in Identifiying Employees Mental Health Problems - Erina Kusuma Widyaningrum; Fatmah Bagis; Naelati Tubastuvi; Meydy Fauziridwan (Jurnal Ilmu Manajemen, 2026)
Worker mental health is an important issue in modern human resource management because it is influenced by work pressure, dual role demands, and the quality of social relationships in the work environment. Based on the Stress-Buffering Model, this study examines how Occupational Stress, Social Support, and Work Family Conflict interact in shaping the mental health conditions of employees at Islamic-based educational institutions. This study aims to analyze the direct influence of Occupational Stress on Mental Health Problems and examine the mediating role of Social Support and Work Family Conflict. A quantitative approach was used through SEM-PLS 3 involving 225 employees of an Islamic Educational Institution in Cilacap Regency who were selected using a purposive sampling technique. The results of the study show that Occupational Stress has a significant positive effect on mental health problems. Occupational Stress has also been shown to decrease Social Support and increase Work Family Conflict. In addition, social support has a significant negative effect on mental health problems, while Work Family Conflict has a significant positive effect. Mediation analysis shows that both act as mediating mechanisms in the relationship between Occupational Stress and Mental Health. These findings strengthen the relevance of the Stress-Buffering Model and emphasize the importance of organizational strategies that focus on strengthening Social Support and creating Work Family role balance to improve Employee Psychological Well-being.